Information and business performance: a study of information systems and services in high-performing companies - T.D. Wilson; I. Owen; A. Abell (Information Research: An International Electronic Journal)
This report focuses on the relationship between information and business performance. Previous work has investigated the relationship between the information culture of a company and its business performance. The Åbo Consortium - a loose affiliation of researchers in the U.K. and the Nordic countries has met from time to time to discuss the development of a collaborative approach to business information research and this project was intended to serve as a model for parallel investigations to be carried out in other countries. The report also builds upon previous work in the business information sector, including a number of studies carried out at the University of Sheffield - particularly the investigation of information needs in business by White and Wilson, which used a case-study approach as does the study reported here.